Introduction to research methods in education - Punch, Keith (SAGE, 2014)
Based on Keith Punch’s bestselling Introduction to Social Research Methods, this book introduces the research process in a range of educational contexts. In this updated second edition, you’ll find guidance on every stage of research, with chapters on developing research questions, doing a literature review, collecting data, analysing your findings and writing it all up.